A Qualitative Endline Evaluation Study of Male Engagement in Promoting Reproductive, Maternal, Newborn, and Child Health Services in Rural Kenya - Lusambili, Adelaide M.; Wisofschi, Stefania; Shumba, Constance; Muriuki, Peter; Obure, Jerim; Mantel, Michaela; Mossman, Lindsay; Pell, Rachel; Nyaga, Lucy; Ngugi, Anthony; Orwa, James; Luchters, Stanley; et al. (Frontiers in Public Health, 2021)
Background: Globally, male involvement in reproductive, maternal, newborn, and child health (RMNCH) is associated with increased benefits for women, their children, and their communities. Between 2016 and 2020, the Aga Khan University implemented the Access to Quality of Care through Extending and Strengthening Health Systems (AQCESS), project funded by the Government of Canada and Aga Khan Foundation Canada (AKFC). A key component of the project was to encourage greater male engagement in RMNCH in rural Kisii and Kilifi, two predominantly patriarchal communities in Kenya, through a wide range of interventions. Toward the end of the project, we conducted a qualitative evaluation to explore how male engagement strategies influenced access to and utilization of RMNCH services. This paper presents the endline evaluative study findings on how male engagement influenced RMNCH in rural Kisii and Kilifi. Methods: The study used complementing qualitative methods in the AQCESS intervention areas. We conducted 10 focus group discussions (FGDs) with 82 community members across four groups including adult women, adult men, adolescent girls, and adolescent boys. We also conducted 11 key informant interviews (KIIs) with facility health managers, and sub-county and county officials who were aware of the AQCESS project. Results: Male engagement activities in Kisii and Kilifi counties were linked to improved knowledge and uptake of family planning (FP), spousal/partner accompaniment to facility care, and defeminization of social and gender roles. Conclusion: This study supports the importance of male involvement in RMNCH in facilitating decisions on women and children's health as well as in improving spousal support for use of FP methods.